Diseño de un sistema de gestión de seguridad y saluda ocupacional aplicado a Moldec S.A. basada en los normas OHSAS - Flores Ortiz, Lisette Marisela (2015)
This thesis was conducted at Moldec S.A., a company engaged in manufacturing of moldings in wood. We are working in the proposal of an implementation in the near future; of which consist of designing a System for Occupational Safety and Health based on OHSAS 18001 standards. This system in addition to creating a sense of responsibility and ownership on the worker for his job can also reduce the number of accidents or illness through the use of prevention and control of risk, reduction of absenteeism and staff rotation. This will also ensure taking advantage of all resources such as time and tools. The endless number of advantages will make the company to have a good execution and thus higher performance. The thesis includes the following: compliance with current legislation, definition of objectives and policies of occupational health and safety hazard identification, as well as risk assessment and control; creating management programs of S & SO to achieve their goals in a given time. Defining tools and deadlines, training, conscientization, challenging workers to strive for success, as well as consultation and communication, documentation and everything else related to operation and documentation control